Incidental corrective feedback by classroom teachers and uptake by bilingual elementary students in teacher-learner interactions - Richel Langit-Dursin (Universitas Katolik Indonesia Atma Jaya, 2016)
The study investigated (1) the relationship between corrective feedback types and errors by bilingual elementary students in speaking; (2) corrective feedback type that leads to high uptake; (3) uptake commonly made by bilingual elementary students in response to incidental corrective feedback; and (4) perspectives of elementary classroom teachers and bilingual young learners on the provision, frequency, and timing of corrective feedback. The qualitative and quantitative research involved classroom teachers from grades 1 to 5 and bilingual elementary students. A total of 20 classroom teachers and 362 elementary students able to speak English, Bahasa Indonesia, and Chinese from a school implementing an international curriculum participated in the research. The study revealed that (1) different corrective feedback types, namely recast, explicit correction, clarification request, metalinguistic feedback, repetition, and elicitation were not specifically linked with phonological, grammatical, and lexical errors in speaking; (2) recast led to high uptake in the form of incorporation but not student-generated repair; (3) repetition was the most common type of uptake by bilingual elementary students; and (4) classroom teachers and elementary students wanted teachers to correct errors and give delayed error correction but have different perspectives on the frequency of doing it. For classroom teachers, learners’ errors have to be corrected all the time but for students, errors have to be corrected sometimes. Peer application of corrective feedback and repeated error by another student are new kinds of uptake based on the results of the classroom-based research.